Antimicrobial Denture Material Synthesized from Poly(methyl methacrylate) Enriched with Cannabidiol Isolates - Kazi Tahsin; William Xu; David Watson; Amin Rizkalla; Paul Charpentier (Molecules)
Cannabidiol (CBD), derived from the Cannabis plant, has shown potential in dentistry for its antimicrobial properties, particularly against oral bacteria. Denture-associated infections, a common issue among denture wearers, present a challenge in antimicrobial enhancements to poly(methyl methacrylate) (PMMA), the primary material for dentures due to its favorable physical and aesthetic qualities. To address this, researchers developed PMMA denture coatings infused with CBD nanoparticles. The CBD coatings were synthesized using UV curing and characterized via 1H NMR, SEM, and FTIR spectroscopies. Antimicrobial activity was assessed against Staphylococcus aureus, Escherichia coli, and Streptococcus agalactiae. CBD demonstrated significant bactericidal effects on Gram-positive bacteria with a minimum inhibitory concentration (MIC) of 2–2.5 µg/mL and a minimum bactericidal concentration (MBC) of 10–20 µg/mL but was ineffective against planktonic Gram-negative bacteria. However, biofilm studies revealed a 99% reduction in biofilm growth for both Gram-positive and Gram-negative bacteria on CBD-infused PMMA compared to standard PMMA. The CBD disrupted bacterial cell walls, causing lysis. Dissolution studies indicated effective release of CBD molecules, crucial for antimicrobial efficacy. This study highlights CBD’s potential for antibiotic-free denture coatings, reducing dental biofilms and plaque formation, and improving oral health outcomes.